The Use of Code Mixing in English Language Teaching (A Study at the Senior High School in Bone Regency) - Wahyu; Atsmar, Muhammad Fadhlil Kholik (LETS: Journal of Linguistics and English Teaching Studies, 2023)
The objective of this research is to investigate the utilization of code mixing by both teachers and students during the instructional and learning activities, as well as to understand the underlying rationales behind their use of code mixing within the context of English classes. This study employs a qualitative approach and utilizes a case study design. The research was conducted among eleventh-grade students at SMAN 1 Bone. Data collection methods included the use of observational field notes and semi-structured interviews. The findings revealed three distinct forms of code mixing employed by both English teachers and students during the teaching and learning process: intra-sentential code mixing, intra-lexical code mixing, and code mixing involving changes in pronunciation. Intra-sentential code mixing emerged as the predominant form utilized by both teachers and students, with 37 instances of intra-sentential code mixing, eight instances of intra-lexical code mixing, and five instances of code mixing involving changes in pronunciation. The reasons underlying students' utilization of code mixing during the teaching and learning process were primarily attributed to their limited vocabulary and their difficulty in speaking English fluently.